Mathematical and algorithmic foundations of the internet - Luccio, Fabrizio, 1938-; Pagli, Linda; Steel, Graham, 1977- (Boca Raton, Fla. : CRC Press, 2012)
'This book introduces the vast wealth of mathematical concepts and methods on which the Internet depends. It illustrates mathematical and algorithmic methods with examples from various fields to show the universality of the concepts presented. The authors provide complete discussions of sequences, exponential growth, algorithms and complexity, randomness, graphs and networks, search engines, parallel and distributed computation, and cryptography. They also address cutting-edge topics, such as game theory, and include a short encyclopedic dictionary of terms related to the Internet'--
'This book is intended to fill the gap between designing and maintaining a computer network--a task for professionals--and even a superficial understanding of its operation. Intended for use in computer science courses at elementary level; or as a suggested reading for students in other fields; or for providing supplementary notions to technical professionals; or, finally, for curious people interested in the advancement of science and technology, the mathematical and algorithmic concepts and methods presented are accompanied by notions coming from literature, history, art, and other fields, to provide a lighter reading experience and to show the universality of many of the concepts treated'--
Includes bibliographical references and index.
Keywords: Internet -- Mathematical models; World Wide Web -- Mathematical models